Indonesian adaptation of the Revised College Student Subjective Wellbeing Questionnaire - Sari Zakiah Akmal; Dewi Kumalasari; Novika Grasiaswaty (HUMANITAS: Indonesian Psychological Journal, 2021)
The College Student Subjective Well-being Questionnaire Revised version (CSSWQ-R) was developed to assess university students' domain-specific well-being related to their academic lives. Previous research suggested that the validity and reliability of this scale should be tested in another cultural context. This study aimed to evaluate the psychometric features and structure of the CSSWQ-R in Indonesia. Five hundred eighty-six undergraduate students in Indonesia were recruited as participants with an accidental sampling technique. Confirmatory factor analysis (CFA) was used to determine which of four alternative construct structure models suited best, whether the correlated factor, single factor, 2nd order, or bifactor model. The bifactor model was shown to be the best fit for explaining the structure of the CSSWQ-R Indonesian version, with the total score interpretation being the most meaningful. Further convergent and discriminant validity test was proven, and as expected, this scale related positively with academic resilience and academic achievement (GPA). This research contributes to stimulating research in an educational context concerned with higher education students' subjective well-being.